Dual-loop integral sliding mode control for robust trajectory tracking of a quadrotor. Issue 2 (25th January 2020) - Wang, Kai; Hua, Changchun; Chen, Jiannan; Cai, Manjun
Abstract : This paper presents a novel control scheme for the trajectory tracking in a quadrotor. First, the kinematics and dynamics models of the quadrotor with uncertainties are developed by Newton–Euler method. For the nonlinear and coupling dynamic, unmodeled uncertainties and external disturbances, an effective linear extended state observer is designed to estimate them. Then, the overall quadrotor system is divided into two subsystems: translational subsystem and rotational subsystem. For the rotational subsystem, the attitude controller is designed with a dual-loop integral sliding mode control method, and the designed controller is able to track the desired attitudes and angular velocities simultaneously. For the translational subsystem, a globally asymptotic stability position controller based on the hyperbolic functions is designed, and the application of hyperbolic functions can provide a bounded and smooth control input. In the end, both simulation and experiment results are provided to verify the effectiveness of the designed control strategy.